Implementasi Pendidikan Multikultural Dalam Meningkatkan Toleransi Pada Pesantren Modern Ummul Quro Al-Islami, Bogor - Syifa Nur Izzati Zahro; Ahmad Dimyati Badruzzaman; Ubaidillah Alghifary Slamet; Ida Ayu Nyoman Saskara (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This study uses a qualitative approach with a case study type of research. Source of data obtained from primary and secondary data. As for data collection techniques using observation, interviews, and documentation. The results of this study indicate that 1) the values ​​of multicultural education for students at the Ummul Quro Al-Islami Modern Islamic Boarding School consist of democratic values, tolerance values ​​and humanism values. 2) Implementation of Multicultural Education in Increasing Tolerance at Ummul Quro Al-Islami Modern Islamic Boarding School, Leuwiliang Bogor, West Java, namely by providing an understanding of multicultural education starting from educators to students, Islamic Boarding Schools have established regulations in terms of using Arabic and English to communicate between students as a multicultural unifying language in Islamic boarding schools, the existence of multicultural-based activities, the application of multicultural education in Islamic boarding schools to increase the tolerance attitude of students through several subjects in class which are conveyed implicitly, providing awareness of the importance of tolerant living by providing lots of advice and reminders conveyed by the Kyai and also educators at Islamic boarding schools. 3) Obstacles in the implementation of multicultural education in increasing tolerance at the Ummul Quro Al-Islami Modern Islamic Boarding School, namely, it takes quite a long time to understand the different characters in the pesantren environment, lack of understanding of the meaning of tolerance in some students, and lack of awareness of the importance of tolerance.